Computational modeling of nanodrug-induced effects on cardiac electromechanics - Shalaby, Noha Mahmoud (AUC Knowledge Fountain, 2016)
This work generally aims to promote the use of computational models for predicting side effects of nanodrugs under development, as a means to speed up the cycle of drug development, with potential savings on testing, and reduction in the need for animal or human testing. The specific objective of this thesis has been to accurately model a single ventricular contraction-relaxation cycle, and monitor the effects induced by nanodrugs on the electro-mechano-physiology of the left and right ventricles. Nanodrug interaction with ion channels located on cardiac cell membranes, such as those for sodium, potassium and calcium, can distort an electrical wave propagating through the tissue and can affect cardiac macroscale functions. In this study, a material model after Holzapfel and Ogden was developed to account for the anisotropic hyperelastic behavior of cardiac tissue, which was implemented on the open source software library Chaste. A coupled drug-electro-mechano-physiological system was then set up, also on Chaste, where a nanodrug effect was introduced into the cellular structure (nanoscale) as an ion channel inhibitor, and its influence then solved for, with respect to resulting electro-mechanical ventricular behaviors. Using quantifiable biomarkers, these effects were compared to the literature and clinical data. In this work we identified the following main results. Nanodrugs causing sodium channel blockage were found to produce the anticipated delays in electro-mechanics. Our study further predicted additional effects on LV twisting and LV & RV strain. On the other hand, nanodrugs causing potassium and calcium channel blockage revealed that cardiac mechanics is less responsive to mild alterations in electrophysiology, than electrophysiology is to ionic changes. Nonetheless, it is important to quantify these changes, as even a very small deviation from normal could accumulate over multiple cardiac cycles, and lead to adverse consequences on cardiac health in the long term.